Forebody wake effects on parachute performance for re-entry space application - Pratap, M.; Agrawal, A.K.; Sati, S.C.; Kumar, V. (Defense Scientific Information and Documentation Centre, 2020)
Forebody generates its own wake that influences the performance of aerodynamic decelerators during the flights. Many parachute Jumpers have experienced the failure of an ejected pilot chute as the parachute canopy collapsed and fell back on the Jumper because of wake developed behind the Jumper. In the available literature, limited data is available to predict the exact loss of parachute drag in presence of the forebody (FB). The purpose of this paper is to generate a comprehensive aerodynamic data to study the behaviour of FB-parachute dynamics by conducting the wind tunnel experiments. Wind tunnel test has been carried out to establish the initial design parameters of aerodynamic parachute. The experiment was carried out on a scale down model of 20 degree conical ribbon drogue parachute and FB with and without each of them at a subsonic speed for studying dynamic stability characteristic for different orientation of FB. The test results indicate that to ensure adequate stability for the capsule to descend vertically at a low subsonic speed, a cluster of two drogue parachutes be used. Under such condition, the overall drag coefficient found to be above 0.50 providing not only a safe descends velocity but increasing reliability of mission as well. © 2020, DESIDOC.
Keywords: Aerodynamic interface data; Coefficient of drag; Forebody; Parachute; Wake effect; Wind tunnel test